Monitoring of KRAS -mutated ctDNA to discriminate pseudo-progression from true progression during anti-PD-1 treatment of lung adenocarcinoma - Guibert, Nicolas; Mazieres, Julien; Delaunay, Myriam; Casanova, Anne; Farella, Magali; Keller, Laura; Favre, Gilles; Pradines, Anne (Oncotarget, 2017)
Pseudo-progression is a rare but worrying situation for both clinicians and patients during immunotherapy. Dedicated ir-RECIST criteria have been established to improve this situation. However, this can be sometimes considered inadequate and patients experiencing true progression may then receive inefficient treatments. Additional reliable tools to discriminate pseudo from true progression are thus needed. So far, no biomarker has been identified to distinguish pseudo from true progression. We hypothesize that biomarkers associated with the molecular characteristics of the tumor may be of interest. To avoid a tumor re-biopsy, circulating markers appear to be a less invasive and reproducible procedure. As ctDNA kinetics correlate with the response to treatment in KRAS-mutated adenocarcinoma, we anticipated that this analysis could be of interest. We monitored the level of KRAS-mutated ctDNA by digital droplet PCR in serial plasma samples from two patients who had experienced pseudo-progression and compared the variations with those from of a patient that had true progression. ctDNA showed rapid and dramatic decreases in pseudo-progressive patients, whereas it was strongly increased in the progressive patient. ddPCR of ctDNA may thus be an additional tool to discriminate pseudo-progression from true progression for tumors that harbor an oncogenic addiction.